2017
DOI: 10.1108/apjml-03-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

Understanding young consumers’ tendencies regarding eco-labelled products

Abstract: Purpose The purpose of this paper is to explore different factors influencing young consumers’ approaches to eco-labeled products in an emerging country, Turkey. Design/methodology/approach Relevant measures were adapted from the previous literature to assess key constructs on environment and eco-label perceptions. First, an exploratory factor analysis was employed for identifying the key dimensions, and then structural equation modeling was conducted for testing the research hypotheses. Findings The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 62 publications
4
32
0
1
Order By: Relevance
“…While [8] who selected college students also found that knowledge on green issues is the second best predictor after environmental atittude to influence green purchasing behavior. It is because consumers with higher environmental knowledge are more conscious towards ecolabels that will assist them in interpreting the information on the labels, thus will influence their purchasing decision [50]. The result is consistent with other researchers such as [8], [20], [21], [41], [48], [51] and [52] that environmental knowledge will lead to consumers' green purchasing behavior.…”
Section: E Knowledgesupporting
confidence: 87%
“…While [8] who selected college students also found that knowledge on green issues is the second best predictor after environmental atittude to influence green purchasing behavior. It is because consumers with higher environmental knowledge are more conscious towards ecolabels that will assist them in interpreting the information on the labels, thus will influence their purchasing decision [50]. The result is consistent with other researchers such as [8], [20], [21], [41], [48], [51] and [52] that environmental knowledge will lead to consumers' green purchasing behavior.…”
Section: E Knowledgesupporting
confidence: 87%
“…In addition, they are a simple way for individuals to identify green products. Eco‐labels are essential for consumers to understand the environmental background of eco‐labeled products or services, thus enabling them to distinguish green products and change their preferences for eco‐labeled products (Göçer & Sevil Oflaç, 2017). Consumers can understand that purchasing eco‐labeled products has a significant environmental impact, while green producers can improve their market share by differentiating their products.…”
Section: Introductionmentioning
confidence: 99%
“…Cont. ,4,5,6,7,8,9,10,11,12,14,16,17,18,19,20,23,25,26,27,28,29,32,34,35,36,37,38,43,46,48,51,52,53,54,55,58,59,60,61,62,63,65,66,68,69,70,71,73,74,77,78,79,80,…”
mentioning
confidence: 99%